An Acid‐Activatable Fluorescence Probe for Imaging Osteocytic Bone Resorption Activity in Deep Bone Cavities. Issue 47 (8th September 2020) - Hashimoto, Ryu; Minoshima, Masafumi; Kikuta, Junichi; Yari, Shinya; Bull, Steven D.; Ishii, Masaru; Kikuchi, Kazuya
Abstract: A rationally designed pH‐activatable fluorescent probe (pHocas‐RIS) has been used to measure localised pH levels in osteocytic lacunae in bone tissue. Conjugation of the moderate bone‐binding drug risedronate to a pH‐activatable BODIPY fluorophore enables the probe to penetrate osteocytic lacunae cavities that are embedded deep within the bone matrix. After injection of pHocas‐RIS, any osteocytic lacunae caused by bone‐resorbing osteocytes cause the probe to fluoresce in vivo, thus allowing imaging by intravital two‐photon excitation microscopy. This pH responsive probe enabled the visualization of the bone mineralizing activities of acid producing osteocytes in real time, thus allowing the study of their central role in remodeling the bone‐matrix in healthy and disease states. Abstract : A pH‐activatable fluorescent probe (pHocas‐RIS) with moderate bone‐binding affinity was synthesized by conjugating a BODIPY fluorophore to bisphosphonate‐targeting risedronate ligands. The probe enabled the imaging of acidic osteocytic lacunae that contain bone resorbing osteocytes in deep bone tissues in living animals.